Representasi Bahasa Promosi dalam Algoritma Media Sosial : Pengenalan Produk dan Penguatan Merek - Dimas Candramulya Santosa; Laurent Cipta Wijaya; Rindu Astuti; Anhar Anhar (GEMILANG: Jurnal Manajemen dan Akuntansi, 2026)
The objective of this research is to determine the extent to which social media algorithms play a role in introducing products to the public while simultaneously strengthening brand image. The problem addressed is that many brands still struggle to reach broader target markets despite utilizing social media platforms. The research methodology employed consists of a literature study examining academic journals related to digital marketing, complemented by simple interviews with entrepreneurs who have established brands through social media. The research findings generally indicate that social media algorithms can assist brands in reaching new audiences, enhancing product visibility, and strengthening brand awareness within society. Through appropriate utilization, social media serves not only as a promotional tool but also as a strategy for building brand image and customer loyalty. This study provides insights into the importance of understanding and applying social media algorithms in building a strong brand image, ultimately fostering sustainable growth, improving customer engagement, and enhancing long-term market presence for brands.